STOCK PRICE ANALYSIS BEFORE AND DURING THE COVID-19 PANDEMIC (Case Study on Pharmaceutical Sub-Sector Listed on the Indonesia Stock Exchange) - Anur, Vera Fitri; Mufid, Jhon Edy; Wulandari, Dwi Siva (Indikator: Jurnal Ilmiah Manajemen dan Bisnis, 2022)
This study aims to analyze the stock prices of the pharmaceutical sub-sector listed in the Indonesia Stock Exchange before and during the Covid-19 pandemic stock price. The background of this research because of the negative effect of the spread of the Covid-19 virus on stock prices. on In this study, the data used are the stock prices of 10 pharmaceutical companies on the Stock Exchange Indonesia quarter II (April-June) The data used is secondary data that can be accessed through yahoo finance and idx stock exchange then the data is processed using the SPSS version 25. The results of processing data on significant differences in stock prices before and during the COVID-19 pandemic.